Capacity-building on competition law and policy for development : a consolidated report (UN New YorkUS, 2008)
Highlights UNCTAD's capacity-building objectives in the area of competition law and policy. Looks at the need for formulating a durable competition policy framework for development and reviews UNCTAD's capacity-building activity. Deals with the COMPAL programme.
Bibliography: p. 39-40